A Case Report of Middle Aortic Syndrome: A Rare Vascular Disorder - Mandal, Naresh Chandra; Hossain, MF; Mamun, AA; Dey, NK; Sabah, MN; Arif, MA; Samad, S; Rahman, MR; Bashar, AHM; Hossain, GMM; Hakim, E; Alam, SAN; et al. (Cardiovascular Journal, 2013)
The middle aortic syndrome (MAS) is rare (about 0.5-2% of all the cases of aortic coarctation) vascular disorder characterized by severe narrowing in the descending thoracic aorta, abdominal aorta, or both. It can be congenital or acquired due to several conditions.MAS may present clinically as uncontrolled hypertension, abdominal angina or lower limb claudication. Surgical treatment is effective in controlling symptom and improves life expectancy. Cardiovascular Journal Volume 6, No. 1, 2013, Page 60-62 DOI: http://dx.doi.org/10.3329/cardio.v6i1.16117